Disability pension granted due to the reduction of prospects for success in the future - Mularski, Krzysztof; Grzesiowski, Krzysztof (Ius Novum, 2023)
The aim of this article is to interpret the conditions for, and the content of, a claim for an appropriate disability pension granted due to the reduction of prospects for success in the future (referred to as the third disability pension condition under Article 444 § 2 of the Civil Code). The chosen subject of analysis is primarily justified by the relative lack of attention this disability pension has received in legal literature compared to pensions granted due to other conditions specified in Article 444 § 2 CC. The authors focus on resolving some of the interpretative doubts in the civil law related to the phrase “reduction of the prospects for success in the future”. The derivative conception of legal interpretation serves as the foundation for their analyses. The article posits that a claim for a pension due to the reduction of prospects for success in the future is available to every natural person (including a conceived child) who has suffered a bodily injury or health disorder resulting in a loss of the ability to work (in the broad sense of the term), including the ability to perform household chores and, consequently, the material or financial benefits such work would provide. According to the authors, the provision’s apparent role is to resolve interpretative doubts regarding the pecuniary benefits that the aggrieved party would likely obtain in the future. This likelihood is higher than low or small, but lower than the probability bordering on certainty (or at least very high), which is the usual requirement for lost benefits in order to be granted a disability pension. This result of the interpretation is fully justified in both functional and systemic interpretative directives, as the legislator, to a certain extent, favours the interests of the person who suffered personal injury over those of the entity responsible for the damage.